Iron Maiden visions of the beast - Iron Maiden (Musical group); Koromubia Myujikku Entateinmento; Sanctuary Visual Entertainment (New York, N.Y. : Columbia Music Entertainment [distributor], 2003)
Complete video history of Iron Maiden's career. Includes 40 minutes of bonus materials and hidden extras
Disc 1 : Women in uniform -- Wrathchild -- Run to the hills -- The number of the beast -- Flight of Icarus -- The trooper -- 2 minutes to midnight -- Aces high -- Wasted years -- Stranger in a strange land -- Can I play with madness -- The evil that men do -- The clairvoyant -- Infinite dreams -- Holy smoke -- Tailgunner. Disc 2 : Bring your daughter to the slaughter -- Be quick or be dead -- From here to eternity -- Wasting love -- Fear of the dark -- Hallowed by thy name -- Man on the edge -- Afraid to shoot strangers -- Lord of the flies -- Virus -- The angel & the gambler -- Futureal -- The wicker man -- Out of the silent planet -- Brave new world.
Keywords: Heavy metal (Music); Rock music